DETERMINAN KEPATUHAN WAJIB PAJAK UMKM CILACAP - Rahman, Kristanti; Anggraeni, Rahayu (JURNAL EKONOMI, 2024)
This study aims to examine the effect of tax awareness (X1), tax sanctions (X2), fiscal attitudes (X3) on taxpayer compliance (Y) in Cilacap UMKM. The sampling technique in this study used non-probability sampling with a sample of 64 respondents. The data collection technique was carried out by distributing questionnaires via Google Forms. The analysis prerequisite tests include normality, linearity, multicollinearity, and heteroscedasticity tests. Data analysis techniques using multiple linear regression. Statistical tests through the T test, R square (R2), and classical assumption tests. Research results: (1) tax awareness affects taxpayer compliance (2) tax sanctions affect taxpayer compliance (3) the attitude of the tax authorities has no effect on mandatory compliance.